Imaginations of Persian Power and Kingship in 1 Esdras: Ancient Jewish Memories of Achaemenid Persia 2 - Häberlein, Maximilian (Journal of Hebrew Scriptures, 2025)
In this paper, the Story of the Three Bodyguards in 1 Esdras 3–4 is related to Persian royal power and rule as imagined in this Hellenistic-period rewriting. First, the presentation of the court is evaluated regarding Hellenistic and Persian elements. The speeches by the first two bodyguards on wine and the king are then read in the context of the book. All three speeches are shown as reflecting the complexities and ambiguities of imperial power and kingship and Judean positions towards it.